Land Use Constraints and Challenges to Sustainable Land Resource Control in Rural Nigeria - Salawu, Busari Morufu (Global Legal Review, 2025)
In Sub Sahara Africa, land occupies an important position in the life of the people. Apart from its important economic value in food security and job creation to millions of rural dwellers, it is sacred and physical. In Nigeria, most of the rural dwellers are into agriculture and pastoralism.  But the constraints on access to land resources under various land tenure systems have created tensions in rural communities and threaten agricultural enterprises. Under these tenures, land resources are not available in the right quantities for varying agricultural purposes as to allow sustainable food security, reduction of poverty, hunger and gender discrimination. The article discusses the concept of land under the various tenure systems; examines land resource control in rural Nigeria and establishes a need for legal reform in land use access and control to ameliorate the constraints. The study adopts a doctrinal research method which relied on primary and secondary sources of information. The article, after establishing that the claim that multiple land tenures and the discriminating policy implementation under the tenures have considerably weakened the land resource control laws, advocates the reforms of the current legal regime to make land resources available to all people needing it for economic development. Transparent and consistent implementation of legal regime, removal of undue delays in the administration of Governor’s consent and streamlining of the incidents of customary land tenure to that of the Land Use Act are suggested.